2005
DOI: 10.1111/j.1440-1754.2005.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of seriously injured children: A study using the Child Health Questionnaire

Abstract: Injured children are worse off than their Australian counterparts in terms of HRQoL even up to 2 years following an injury. Further research needs to be undertaken to identify factors that predict lower HRQoL in order to reduce the burden of injury on children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…Qualitative interviews allowed in-depth exploration of the experiences and insights of New Zealand families as they encountered and moved through the hospital system with their injured child. This approach provided depth and richness not captured in quantitative research undertaken overseas (Harris et al 1989, Wesson et al 1992, Davey et al 2005, Kenardy et al 2006.…”
Section: Discussionmentioning
confidence: 98%
“…Qualitative interviews allowed in-depth exploration of the experiences and insights of New Zealand families as they encountered and moved through the hospital system with their injured child. This approach provided depth and richness not captured in quantitative research undertaken overseas (Harris et al 1989, Wesson et al 1992, Davey et al 2005, Kenardy et al 2006.…”
Section: Discussionmentioning
confidence: 98%
“…The quality of life enjoyed by the patients did not differ from a healthy reference population. Winthrop [6,[19][20][21][22]. In these studies, a lower quality of life was also found in children within 2 years after trauma compared to healthy reference groups.…”
Section: Introductionmentioning
confidence: 94%
“…Ана-логичные результаты были получены T.M. Davey et al, установившими, что и через 2 года после травмы показатели качества жизни (по CHQ) остаются ниже популяционных норм [53].…”
Section: обзоры литературыunclassified